The European illustrated press and the emergence of a transnational visual culture of the news, 1842-1870 - Smits, Thomas (Routledge studies in modern European history, 2020)
"This book looks at the roots of a global visual news culture: the trade in illustrations of the news between European illustrated newspapers in the mid-nineteenth century. In the age of nationalism, we might suspect these publications to be filled with nationally produced content, supporting a national imagined community. However, the large-scale transnational trade in illustrations, which this books uncovers, points out that nineteenth century news consumers already looked at the same world. By exchanging images, European illustrated newspapers provided them with a shared, transnational, experience"--